When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren
This study examines the visibility of the GAAP effective tax rate (ETR) in firms’ financial statements as a distinct disclosure choice. Applying a game-theory disclosure model for voluntary disclosure strategies of firms to a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders “favourable conditions”, for example in terms of higher expected after-tax cash-flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, decreasing). Additional analyses reveal that this high visibility is characteristic of firm-years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms do not seem to highlight favourable ETRs.

Steuerliche Maßnahmen als nützliches Mittel zur Bewältigung der Corona-Krise? - Ergebnisse einer Unternehmensbefragung - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (Deutsches Steuerrecht)

Umfrage: Steuerliche Verwaltungskosten, steuerliche Corona-Soforthilfemaßnahmen und Investitionen in der Krise - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Tax Complexity in Australia – a Survey-Based Comparison to the OECD Average - Hoppe, Thomas (Australian Tax Forum)
This article comprehensively reviews Australia’s corporate income tax complexity as faced by multinational corporations (MNCs) and compares it to the average of the remaining OECD countries. Building on unique survey data, I find that the Australian tax code is considerably more complex than the OECD average, which is mainly due to overly complex anti-avoidance legislation, such as regulations on transfer pricing, general anti-avoidance or controlled foreign corporations (CFC). In contrast, Australia’s tax framework, which covers processes and features such as tax law enactment or tax audits, is close to the OECD average. A more detailed analysis yields further interesting insights. For example, excessive details in the tax code and the time between the announcement of a tax law change and its enactment turn out to be serious issues in Australia relative to the remaining OECD countries.

Tax Complexity in Australia - A Survey-Based Comparison to the OECD Average - Hoppe, Thomas
This article comprehensively reviews Australia’s corporate income tax complexity as faced by multinational corporations (MNCs) and compares it to the average of the remaining OECD countries. Building on unique survey data, I find that the Australian tax code is considerably more complex than the OECD average, which is mainly due to overly complex anti-avoidance legislation, such as regulations on transfer pricing, general anti-avoidance or controlled foreign corporations (CFC). In contrast, Australia’s tax framework, which covers processes and features such as tax law enactment or tax audits, is close to the OECD average. A more granular analysis yields further interesting insights. For example, excessive details in the tax code and the time between the announcement of a tax law change and its enactment turn out to be serious issues in Australia relative to the remaining OECD countries.

2018 Global MNC Tax Complexity Survey - Hoppe, Thomas; Schanz, Deborah; Schipp, Adrian; Siegel, Felix; Sturm, Susann; Sureth-Sloane, Caren

Measuring Tax Complexity Across Countries: A Survey Study on MNCs - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that comprehensively measures the complexity of countries’ corporate income tax systems faced by multinational corporations. It builds on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries, we find that tax complexity varies considerably across countries, and tax code and framework complexity also vary within countries. Among others, tax complexity is strongly driven by the complexity of transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different patterns. For example, with regard to GDP, we find a positive association with tax code complexity and a negative association with tax framework complexity, suggesting that highly economically developed countries tend to have more complex tax codes and less complex frameworks. Overall, our tax complexity measures can serve as valuable proxies in future research and supportive tools for a variety of firm decisions and national and international tax policy discussions.

The Relation between Tax Complexity and Foreign Direct Investments: Evidence Across Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren; Voget, Johannes
This paper analyzes the association between tax complexity and foreign direct investments (FDI) based on the newly developed Tax Complexity Index (TCI) and its components. For a sample of 15,607 new foreign subsidiaries, we find no association between total tax complexity, as proxied by the TCI, and the location probability. When we decompose the TCI into tax code complexity and tax framework complexity, we find opposing associations. Tax code complexity is positively related to the location probability, while tax framework complexity is negatively related to it. These associations are, for example, driven by the complexity of transfer pricing and loss offset regulations in the tax code and the dimensions guidance, audits, as well as filing and payments, in the tax framework. In additional analyses, we find that the associations are sensitive to certain characteristics, such as country-specific and firm-specific characteristics. For example, the positive tax code association diminishes when tax rates are high. Overall, we are the first to provide empirical evidence on potential cost-benefit tradeoffs of tax complexity for FDI and thereby enhance prior literature, which has primarily focused on the costs of tax complexity.

Steuerkomplexität als Standortfaktor. So komplex ist das Steuersystem in Deutschland - Sureth-Sloane, Caren (AWV-Informationen)

Evaluation of a ReconOS-ROS Combination based on a Video Processing Application - Henke, Luca-Sebastian
Robots are becoming increasingly autonomous and more capable. Because of a limited portable energy budget by e.g. batteries, and more demanding algorithms, an efficient computation is of interest. Field Programmable Gate Arrays (FPGAs) for example can provide fast and efficient processing and the Robot Operating System (ROS) is a popular middleware used for robotic applications. The novel ReconROS combines version 2 of the Robot Operating System with ReconOS, a framework for integrating reconfigurable hardware. It provides a unified interface between software and hardware. ReconROS is evaluated in this thesis by implementing a Sobel filter as the video processing application, running on a Zynq-7000 series System on Chip. Timing measurements were taken of execution and transfer times and were compared to theoretical values. Designing the hardware implementation is done by C code using High Level Synthesis and with the interface and functionality provided by ReconROS. An important aspect is the publish/subscribe mechanism of ROS. The Operating System interface functions for publishing and subscribing are reasonably fast at below 10 ms for a 1 MB color VGA image. The main memory interface performs well at higher data sizes, crossing 100 MB/s at 20 kB and increasing to a maximum of around 150 MB/s. Furthermore, the hardware implementation introduces consistency to the execution times and performs twice as fast as the software implementation.

CONSENS 3D: Method for 3D-Environment Driven Domain Knowledge Elicitaion and System Model Generation - Japs, Segej; Kharatyan, Aschot; Kaiser, Lydia; Dumitrescu, Roman (Proceedings of the 16th International Design Conference (DESIGN 2020))

Towards a modular product architecture for electric ferries using Model- Based Systems Engineering - Pfeifer, Stefan; Seidenberg, Tobias; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman (Procedia Manufacturing)

Scenarios in the Loop: Integrated Requirements Analysis and Automotive System Validation - Wiecher, Carsten; Japs, Sergej; Kaiser, Lydia; Greenyer, Joel; Wolff, Carsten; Dumitrescu, Roman (ACM/IEEE 23rd International Conference on Model Driven Engineering Languages and Systems (MODELS ’20 Companion))

Verification of Mathematical Model for Upper Limb Spasticity with Clinical Data - Yee, Jingye; Low, Cheng Yee; Ong, P.; Soh, WS; Hannapiah, Fazah Akhtar; Zakaria, NC; von Enzberg, Sebastian; Asmar, Laban; Dumitrescu, Roman (IOP Conference Series: Materials Science and Engineering)

Combined Curing and Forming of Fiber Metal Laminates - Heggemann, Thomas; Homberg, Werner; Sapli, Hüseyin (Procedia Manufacturing)

Automating test schedule generation with domain-specific languages - Anjorin, Anthony; Weidmann, Nils; Oppermann, Robin; Fritsche, Lars; Schürr, Andy (Proceedings of the 23rd ACM/IEEE International Conference on Model Driven Engineering Languages and Systems, MODELS 2020)

A search-based and fault-tolerant approach to concurrent model synchronisation - Weidmann, Nils; Fritsche, Lars; Anjorin, Anthony (Proceedings of the 13th ACM SIGPLAN International Conference on Software Language Engineering, SLE 2020)

VICToRy: Visual Interactive Consistency Management in Tolerant Rule-based Systems - Weidmann, Nils; Anjorin, Anthony; Cheney, James (Proceedings of the Eleventh International Workshop on Graph Computation Models, GCM@STAF 2020)

A Model-Driven Mutation Framework for Validation of Test Case Migration - Jovanovikj, Ivan; Weidmann, Nils; Yigitbas, Enes; Anjorin, Anthony; Sauer, Stefan; Engels, Gregor (Proceedings of the First International Conference on Systems Modelling and Management, ICSMM 2020)

AI Marketplace – The Ecosystem for Artificial Intelligence in Product Creation (ERCIM News)